Radial symmetry of a relativistic Schrödinger tempered fractional p-Laplacian model with logarithmic nonlinearity - Hou, Wenwen; Zhang, Lihong (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, by introducing a relativistic Schrödinger tempered fractional p-Laplacian operator (–Δ)p,λs,m, based on the relativistic Schrödinger operator (–Δ + m2)s and the tempered fractional Laplacian (Δ + λ)β/2, we consider a relativistic Schrödinger tempered fractional p-Laplacian model involving logarithmic nonlinearity. We first establish maximum principle and boundary estimate, which play a very crucial role in the later process. Then we obtain radial symmetry and monotonicity results by using the direct method of moving planes.
Keywords: relativistic Schrödinger tempered fractional p-Laplacian operator; direct method of moving planes; logarithmic nonlinearity; radial symmetry and monotonicity